Subject teacher education as a prisoner of its own tradition: Experiments in mathematics and science to break out of the routine - Harry Silfverberg (Tampere University Press, 2022)
Introduction
In Finland, mathematics, physics, chemistry and information technology are usually referred to as mathematical subjects. This chapter introduces four reforms concerning the subject teacher education programmes in the mathematical subjects carried out in the School of Education at the University of Tampere during the last two decades. Each of these reforms in their own way challenged the traditional ideas of what type of structure the subject teacher education programme should and could have, what contents it should have, and which institutions should be responsible for the administration of each sector of the education. In this chapter, my aim is to examine, as objectively as possible, the motives leading to the onset of these development projects, the basic ideas behind the projects and the life course of each project. Some of the projects are still ongoing, some of them have ended and others will end soon. However, one must remember that although projects end, many of their innovative background ideas continue their lives in some other form in the practices of the institution. As far as the completed projects are concerned, we also examine the reasons leading to the end of the projects despite having had quite a general agreement on the value and innovativeness of the experiments.
The contents of the curriculum for subject teacher education are checked and modified at intervals of two or three years, the purpose of which is to renew the entire curriculum of the teacher education unit. Nevertheless, from earlier curricula, one can notice that the basic structure of the curriculum has remained almost unchanged for a surprisingly long time. Subject teacher education has a strong tradition that seems to resist changes that may be too radical but perhaps changes that would be necessary and perhaps even de rigueur. For a long time, slightly more than one third of the pedagogic studies (60 ETCS) has consisted of basic studies in (general) education, about one third teaching practice, and the rest, i.e. slightly less than one third, consists of subject didactic studies. However, several different issues have created pressure to change subject teacher education – even quite radically – and especially in mathematical subjects. The pressure has targeted both reforming the structures of subject teacher education programmes and developing the contents of individual courses within the programme.
Subject Teacher Education in Transition : Educating Teachers for the Future